Titanium alloy cutting fluid and preparation method thereof
By using trimethylolpropane oleate and neopentyl glycol oleate as base oil in titanium alloy cutting fluid, combined with nanolubrication and wetting fillers, the problem of insufficient cooling and lubrication performance of the existing cutting fluid is solved, and more efficient titanium alloy cutting processing is achieved.
Patent Information
- Application Number
- CN202510071691.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing titanium alloy cutting fluid has shortcomings in cooling performance and lubrication performance, and it is difficult to meet the demand for efficient cooling and lubrication of titanium alloy cutting processing.
Trimethylolpropane oleate and neopentyl glycol oleate are used as base oil, and nano-lubricating fillers and nano-wetting fillers are added. Titanium alloy cutting fluid is prepared by ultrasonic stirring and homogenization treatment, and the pH value is adjusted to 8-10 to improve stability.
It significantly improves the lubricating and cooling performance of cutting fluid, extends service life, reduces tool wear, and improves the quality of processing surfaces.
Smart Images

Figure CN119875729A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal cutting fluids, and in particular to a titanium alloy cutting fluid and a preparation method thereof. Background Art
[0002] Titanium alloy has excellent properties such as high specific strength, strong corrosion resistance, good biocompatibility and low temperature resistance. However, as a typical difficult-to-machine material, its cutting process will cause the temperature in the cutting area to be too high, which can easily damage the tool and the surface of the workpiece. Currently, cutting fluid is used to alleviate the above situation.
[0003] Cutting fluid is a liquid used for cooling and lubrication during the metal cutting process. It needs to have good cooling and lubrication properties. Currently, cutting fluids mainly include two categories: oil-based cutting fluids and water-based cutting fluids. Oil-based cutting fluids have the advantage of good lubricity, but poor cooling properties, and are prone to produce oil mist and oil smoke, posing a flammable hazard. Water-based cutting fluids have high cooling properties, but their lubricity is not as good as oil-based cutting fluids, and they are easy to deteriorate.
[0004] The existing patent with authorization announcement number CN 102876441 B discloses an environmentally friendly titanium alloy microemulsified cutting fluid. The cutting fluid adopts new base oil and additives, and the obtained product has stable quality, safety, and environmental protection, and the service life is generally more than one year; the main problem solved is to improve the long-term preservation ability of the cutting fluid, and its components that have a lubricating effect all belong to conventional technologies, and no relevant improvement is given to improving the cooling performance and lubrication performance of the cutting fluid.
[0005] However, in actual use, the lubrication and cooling ability of the cutting fluid is of great significance for titanium alloy cutting, and is an important condition for reducing tool wear and improving the quality of processed surface. Therefore, in order to obtain a cutting fluid with good cooling and lubrication properties, we propose a titanium alloy cutting fluid and its preparation method. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiencies mentioned in the above background technology and to provide a titanium alloy cutting fluid and a preparation method thereof.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A titanium alloy cutting fluid, wherein the mass fractions of each component are specifically:
[0009]
[0010] Preferably, the pH value of the titanium alloy cutting fluid is set to 8-10.
[0011] Preferably, the pH regulator for adjusting the pH value of the titanium alloy cutting fluid adopts any one of triethanolamine, diethanolamine, diglycolamine and ethanolamine as an organic base.
[0012] Preferably, the base oil is trimethylolpropane oleate and neopentyl glycol oleate in a mass ratio of 1:0.2-1.
[0013] Preferably, the nano-lubricating filler is any one of molybdenum disulfide, tungsten disulfide and graphite with a particle size of 20-60nm.
[0014] Preferably, the nano wetting filler is silicon dioxide with a particle size of 20-60 nm.
[0015] Preferably, the emulsifier is any one of oleyl alcohol polyoxyethylene ether 1602, oleyl alcohol polyoxyethylene ether 1605, polyethylene glycol 400, and polyethylene glycol 600.
[0016] A method for preparing a titanium alloy cutting fluid, the specific steps of the preparation method are:
[0017] Step 1: pretreatment of fillers, mixing nano-wetting fillers and nano-lubricating fillers into deionized water according to mass fractions, and adding dispersants;
[0018] Step 2: Ultrasonic stirring treatment, applying ultrasonic power of 200-500W, 500-1000r / min stirring treatment for 30-60min to obtain a dispersion;
[0019] Step 3: pre-mixing, adding the emulsifier to the dispersion, and simultaneously applying stirring at 200-500 r / min to obtain an emulsifier aqueous solution;
[0020] Step 4: Add base oil, drop the base oil into the emulsifier aqueous solution at a dropping speed of 1-5 ml / min, and simultaneously apply stirring at 500-800 r / min to form a preliminary emulsion;
[0021] Step 5: Add additives, add lubricants, corrosion inhibitors, rust inhibitors, defoamers, and fungicides into the preliminary emulsion, stir at 500-800 r / min, and add organic base to adjust the pH to 8-10 to obtain titanium alloy cutting fluid.
[0022] Preferably, the dispersant is sodium dodecylbenzene sulfonate accounting for 0.5-3% of the total mass of the nano wetting filler and the nano lubricating filler.
[0023] Preferably, the titanium alloy cutting fluid in step five is subjected to homogenization treatment, a homogenizer is used to apply a pressure of 20-50 MPa, and the homogenization treatment is performed 2-5 times.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The titanium alloy cutting fluid and its preparation method use a base oil with lubricity and antioxidant stability, which can improve the antioxidant stability of the cutting fluid and is conducive to maintaining the long-term use of the cutting fluid;
[0026] 2. The nano-lubricating filler can improve the lubrication performance and thermal cooling performance of the cutting fluid, which is beneficial to reduce the temperature of the workpiece surface and reduce friction during cutting;
[0027] 3. The nano-wetting filler combined with the nano-lubricating filler can effectively reduce the contact angle, improve the wetting performance between the cutting fluid and the workpiece, which is conducive to better wetting the workpiece surface and improving the use effect of the cutting fluid; overall, the cutting fluid has good lubrication and cooling properties, and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0029] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0031] See also Figure 1 The present invention describes the above technical solution in detail through the following embodiments:
[0032] Example 1
[0033] A titanium alloy cutting fluid, wherein the mass fractions of each component are specifically:
[0034]
[0035]
[0036] In this embodiment, trimethylolpropane oleate and triethanolamine are purchased from BASF, neopentyl glycol oleate is purchased from Huizhou Keli Chemical Co., Ltd., oleyl alcohol polyoxyethylene ether 1602 is purchased from An Yi Chemical (Jiangsu) Co., Ltd., lubricant DX529, corrosion inhibitor DX5810 and rust inhibitor DX309 are all purchased from Dexu New Materials (Guangzhou) Co., Ltd., molybdenum disulfide, tungsten disulfide, and graphite are purchased from Shanghai Huahe New Materials Co., Ltd. with a specification of 30nm, silicon dioxide is purchased from Zhejiang Yamei Nano Technology Co., Ltd. with a specification of 30nm, defoamer is purchased from Suzhou Qingtian New Materials Co., Ltd., and the solid content is 45% of the DH-2170S product is sold, and the bactericide is purchased from Foshan Lanfeng Additive Co., Ltd., and the JS-3006 product is sold.
[0037] Specifically, the base oil in this embodiment uses trimethylolpropane oleate and neopentyl glycol oleate in a mass ratio of 1:0.5; trimethylolpropane oleate contains multiple hydroxyl groups and ester groups in its molecular structure, has excellent lubricity and wear resistance, can adhere well to the surface of titanium alloy and tool, and effectively reduce the friction during the cutting process; neopentyl glycol oleate has good antioxidant properties, can resist oxidation reactions during the use of the cutting fluid, extend the service life of the cutting fluid, and slow down the deterioration of the cutting fluid.
[0038] It should be noted that the present application creatively introduces nano-wetting fillers for preparing cutting fluids with good cooling and lubricating properties; however, nano-silicon dioxide as a nano-wetting filler has poor thermal conductivity and a hard texture, and does not have lubrication and cooling properties itself. Therefore, conventional technical means do not associate it with lubrication and cooling properties, but this component is necessary in the present application; in addition, nano-lubricating fillers are synergistically arranged, and their molybdenum disulfide, tungsten disulfide, and graphite themselves have excellent thermal conductivity and self-lubricating properties, which can improve the cooling and lubrication capabilities of the cutting fluid, and the above-mentioned properties depend on the structural characteristics of the nano-lubricating fillers and are not affected by the ambient temperature of use.
[0039] The steps of the preparation method of the titanium alloy cutting fluid in this embodiment are as follows:
[0040] Step 1: filler pretreatment, 30nm molybdenum disulfide and 30nm silicon dioxide are mixed into deionized water according to the mass fraction, and sodium dodecylbenzene sulfonate accounting for 3% of the total mass of the nano-wetting filler and the nano-lubricating filler is added as a dispersant; the dispersant can generate electrostatic repulsion on the surface of 30nm molybdenum disulfide and 30nm silicon dioxide to avoid agglomeration between particles and achieve dispersion;
[0041] Step 2: Ultrasonic stirring treatment: in order to improve the uniform and stable dispersion of 30nm molybdenum disulfide and 30nm silicon dioxide as solid particles, an ultrasonic power of 500W is applied and the stirring treatment is carried out at 1000r / min for 30min to obtain a dispersion liquid;
[0042] Step 3: pre-mixing, adding the emulsifier oleyl alcohol polyoxyethylene ether 1602 into the dispersion, and simultaneously applying stirring at 500 r / min to obtain an emulsifier aqueous solution;
[0043] Step 4: adding base oil, mixing trimethylolpropane oleate and neopentyl glycol oleate and dropping them into the emulsifier aqueous solution at a dropping speed of 3 ml / min, and simultaneously applying 500 r / min stirring to form a preliminary emulsion; this process can make the base oil gradually dispersed in water under the action of the emulsifier to form an emulsion, and the speed of dropping the base oil should not be too fast. If the dropping speed is too fast, it is easy to cause the local oil phase concentration of the emulsion to be too high, and the emulsifier will not have time to completely wrap the oil droplets, which may cause the oil droplets to aggregate, thereby causing the emulsion to be unstable or even demulsified; the dropping speed of the present application can make the base oil fully dispersed in the emulsifier aqueous solution to form a stable emulsion;
[0044] Step 5: Add additives, add lubricant DX529, corrosion inhibitor DX5810, rust inhibitor DX309, defoamer DH-2170S, and fungicide JS-3006 to the preliminary emulsion, stir at 500 r / min for 5 minutes, add organic base triethanolamine to adjust the pH to 9, and continue stirring for 25 minutes;
[0045] It should be explained that the pH regulator for adjusting the pH value of the titanium alloy cutting fluid adopts triethanolamine as an organic base. The pH value is limited to the range of 8-10 in this application, which can not only effectively inhibit the reproduction of microorganisms such as bacteria and molds, but also help maintain the stability of the cutting fluid; at the same time, the pH value is adjusted to avoid the problem of decomposition of the lubricant DX529 in an acidic environment.
[0046] Step 6: Homogenization. The emulsion of step 5 is homogenized 5 times by applying a pressure of 35 MPa through a Niro Soavi high-pressure homogenizer. The purpose of the homogenization process is to prevent phase separation. In the emulsion system, the homogenization process can obtain a more uniform dispersion effect, effectively prevent the phase separation of the emulsion, and delay the separation of the oil phase and the water phase of the emulsion.
[0047] Example 2
[0048] The difference between this embodiment and embodiment 1 is that the base oil in this embodiment is composed of trimethylolpropane oleate and neopentyl glycol oleate in a ratio of 1:0.2, that is, 20 parts of trimethylolpropane oleate and 4 parts of neopentyl glycol oleate, and other conditions are the same.
[0049] Example 3
[0050] The difference between this embodiment and embodiment 1 is that the base oil in this embodiment is composed of trimethylolpropane oleate and neopentyl glycol oleate in a ratio of 1:1, that is, 20 parts of trimethylolpropane oleate and 20 parts of neopentyl glycol oleate, and other conditions are the same.
[0051] Example 4
[0052] The difference between this embodiment and embodiment 1 is that in this embodiment, 10 parts of 30 nm tungsten disulfide are used as nano-lubricating fillers, and other conditions are the same.
[0053] Example 5
[0054] The difference between this embodiment and embodiment 1 is that in this embodiment, 10 parts of 30 nm graphite are used as nano-lubricating filler, and other conditions are the same.
[0055] Example 6
[0056] The difference between this embodiment and embodiment 1 is that in this embodiment, 5 parts of 30 nm molybdenum disulfide are used as nano-lubricating fillers, and other conditions are the same.
[0057] Example 7
[0058] The only difference between this embodiment and embodiment 1 is that in this embodiment, 3 parts of 30 nm silicon dioxide are used as nano wetting fillers, and other conditions are the same.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that no nano-lubricating filler and nano-wetting filler are added in this comparative example, and other conditions are the same.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that the base oil in this comparative example is composed of 30 parts of trimethylolpropane oleate, and other conditions are the same.
[0063] Comparative Example 3
[0064] The difference between this comparative example and Example 1 is that the base oil in this comparative example is composed of 30 parts of neopentyl glycol oleate, and other conditions are the same.
[0065] Comparative Example 4
[0066] The difference between this comparative example and Example 1 is that 15 parts of 30 nm tungsten disulfide are used as nano-lubricating filler in this comparative example, and other conditions are the same.
[0067] Comparative Example 5
[0068] The difference between this comparative example and Example 1 is that 30 nm tungsten disulfide as a nano-lubricating filler is not added in this comparative example, and other conditions are the same.
[0069] Comparative Example 6
[0070] The difference between this comparative example and Example 1 is that 10 parts of 30 nm silicon dioxide are used as nano wetting filler in this comparative example, and other conditions are the same.
[0071] Comparative Example 7
[0072] The only difference between this comparative example and Example 1 is that 30 nm silicon dioxide as a nano wetting filler is not added in this comparative example, and other conditions are the same.
[0073] Comparative Example 8
[0074] The difference between this comparative example and Example 1 is that in this comparative example, the organic base triethanolamine is not used to adjust the pH value, and sodium hydroxide purchased from MacLean reagent CAS No. 1310-73-2 is used to prepare a 5wt% solution to adjust the pH value, and other conditions are the same.
[0075] Sample cutting fluids were prepared according to Examples 1-7 and Comparative Examples 1-8, and the following performance tests were performed respectively. Three groups of effective values were tested in parallel and the average value was calculated and recorded. The specific performance tests and their steps are as follows:
[0076] (1) Lubrication performance test
[0077] The tapping torque value of TC4 titanium alloy was tested using a microtap TTT tapping torque machine. The tapping torque test conditions were: tapping speed 500r / min, extrusion tapping, tapping depth 20mm, tapping hole diameter 3.7mm, and the average tapping torque value (N·cm) was tested. The lower the average tapping torque value, the better the lubricity.
[0078] (2) Wettability test
[0079] When a liquid substance comes into contact with a solid surface, the liquid substance will spread on the solid surface. The ability of the liquid to spread on the solid surface is the wettability. The wettability is determined by the steady-state contact angle of the droplet of the measured liquid on the solid surface. The smaller the contact angle, the easier it is for the liquid to adhere to and spread on the solid surface, and the better it can wet the solid surface.
[0080] (3) Cooling performance test
[0081] Under the room temperature of 23±2℃, the peak temperature of each cutting fluid during the cutting process was tested to determine the cooling performance. The test conditions were: turning a TC4 titanium alloy rod with a diameter of 1cm and a length of 10cm, a lathe spindle turning speed of 60m / min, a turning length of 5cm and a depth of 2mm, and applying a cutting fluid of 15L / min. After the turning process was completed, the section temperature was tested within 2S, and the average value was calculated after three tests.
[0082] (4) Stability performance test
[0083] 4.1. Storage stability test: refer to the test conditions of GB / T 6144 "Synthetic Cutting Fluid", take 50ml sample and place it in a 100ml stoppered measuring cylinder, place it in a 70±3℃ constant temperature drying oven for 5h, take it out and cool it to 23±2℃ for 3h, then place it in a -12±3℃ low temperature refrigerator for 24h, take it out and let it stand at 23±2℃ for 1h, observe whether there is stratification and phase change, and judge the storage stability;
[0084] 4.2. Antioxidant stability test: Take a cutting fluid sample, introduce oxygen continuously at 50 ml / min at 75°C, and stir continuously to ensure that oxygen and cutting fluid are in full contact. Observe whether the sample is stratified or undergoes phase change after 24h, 48h, and 72h to determine the antioxidant stability.
[0085] In the above 4.1 and 4.2, if the stability is good and there is no stratification or phase change, it is recorded as "uniform" in the table; if stratification and phase change occur, it is recorded as "stratified";
[0086] The specific data is as follows:
[0087] Table 1:
[0088]
[0089] Table 2:
[0090]
[0091] According to the data in Table 1 and Table 2, it can be seen from the data in Reference Example 2 and Example 3 that the content of neopentyl glycol oleate decreases, resulting in a decrease in the total amount of base oil, and the amount of base oil is positively correlated with lubricity; however, in Example 3, as the content of neopentyl glycol oleate increases, the contact angle increases, and the section temperature is higher than that in Example 1, which means that the lubricity is improved, but the cooling performance is obviously attenuated. Considering its comprehensive performance, the formula ratio of excessive neopentyl glycol oleate is not adopted;
[0092] According to the data of Comparative Examples 2 and 3, the total amount of base oil remains unchanged, and the trimethylolpropane oleate and neopentyl glycol oleate will affect the performance of the cutting fluid when used alone: the cooling property and lubricity of the base oil composed of 30 parts of trimethylolpropane oleate in Comparative Example 2 are similar to those of Example 1, and the lubricity is slightly improved, but its antioxidant stability is not good, and stratification occurs after 48 hours; and the base oil composed of 30 parts of neopentyl glycol oleate in Comparative Example 3, although the antioxidant stability is good, its lubricity is significantly reduced, the contact angle is significantly increased, and the cooling performance is also significantly attenuated; considering the above, the neopentyl glycol oleate in the base oil has an effect on the antioxidant stability, but the lubricity and the performance of improving the contact angle are not as good as those of trimethylolpropane oleate, and the two can cooperate to obtain a cutting fluid with balanced lubricity and antioxidant stability;
[0093] In Example 4 and Example 5, different types of nano-lubricating fillers were selected. In combination with Example 1, molybdenum disulfide, tungsten disulfide and graphite as nano-lubricating fillers were able to obtain smaller contact angles and good lubrication performance. Their thermal conductivity was slightly different, which was considered to be caused by the difference in the thermal conductivity physical properties of the nano-lubricating fillers themselves. Among them, the contact angles of molybdenum disulfide and graphite were similar, and the section temperatures were similar, but there was a difference in the tapping torque values. It was considered that the lubrication performance of the tapping torque value was affected by the lubrication physical properties of the nano-lubricating fillers. From the data, the lubrication performance was tungsten disulfide, molybdenum disulfide and graphite in order, and tungsten disulfide had the best lubrication effect.
[0094] According to the data of Comparative Examples 4 and 5, the excessive tungsten disulfide in Comparative Example 4 leads to a larger contact angle, but the lubricity and cooling performance are improved. It is considered that the thermal conductivity and lubricity of tungsten disulfide are affected, but it is found that the cutting fluid stability of Comparative Example 4 is poor, and stratification occurs; in Comparative Example 5, no nano-lubricating filler is added, which obviously causes the lubricity and cooling performance to decay, but the cutting fluid has good stability, and it is found that the contact angle is larger than that of Example 1. It is considered that the content of the filler will affect the contact angle of the cutting fluid and affect the wetting performance; in combination with Example 6 of the present application, the content of molybdenum disulfide is reduced, the lubricity is deteriorated, the contact angle is slightly larger, but the temperature of the section increases significantly, indicating that molybdenum disulfide can conduct heat and cool down while playing a lubricating role, thereby obtaining a cooling effect;
[0095] Example 7 and Comparative Example 6 and Comparative Example 7 make data analysis on the content of nano wetting filler, wherein the data of Example 7 show that the reduction of nano silicon dioxide content can improve lubricity, but its contact angle becomes significantly larger, and its section temperature increases slightly; Comparative Example 7 shows that the nano wetting filler silicon dioxide affects the contact angle and wettability, and its absence leads to an increase in the contact angle and a decrease in the performance of the cutting fluid; the excessive silicon dioxide filler in Comparative Example 6 leads to an increase in the contact angle, poor wettability, and a significant decrease in lubricity, and the cooling effect is significantly attenuated. At the same time, the stability of the cutting fluid is poor, which is considered to be caused by the high proportion of fillers. Therefore, excessive fillers will lead to poor wettability, which also proves that excessive nano lubricating fillers will affect the contact angle and destroy the stability of the cutting fluid. Therefore, the proportion of nano wetting fillers and nano lubricating fillers in this application is crucial, and the improvement of wettability within the scope of this application can obtain good lubricity and cooling;
[0096] Comparative Example 1 is a blank control, indicating that without adding nano-lubricating fillers and nano-wetting fillers, the lubricity and cooling performance will be seriously attenuated, and the contact angle is large, and the wetting performance is poor; Comparative Example 8 shows that the use of inorganic alkali has little effect on the cooling and lubricity of the cutting fluid, but directly affects the stability, resulting in stratification, and the long-term use is poor, which does not meet the actual use requirements;
[0097] In summary, the base oil in the present application creatively uses trimethylolpropane oleate and neopentyl glycol oleate, which obtains lubricity while improving the antioxidant stability of the cutting fluid; and the present application creatively uses nano-wetting fillers to greatly reduce the contact angle and improve the wetting performance. By improving the wettability, the cutting fluid can better infiltrate the titanium alloy surface. The data shows that the lubrication and cooling performances are improved, and the use effect of the cutting fluid is effectively improved; and the nano-lubricating fillers are indispensable to provide lubrication and heat-conducting media. In the present application, attention should be paid to the amount of filler. The contact angle does not decrease continuously with the addition of filler, but will suddenly increase when the amount is excessive. Therefore, excessive addition is not used, and Example 4 can be selected according to cutting requirements to prepare the cutting fluid.
[0098] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A titanium alloy cutting fluid, characterized in that: The specific mass fractions of each component are:
2. The titanium alloy cutting fluid according to claim 1, characterized in that: The pH value of the titanium alloy cutting fluid is set to 8-10.
3. The titanium alloy cutting fluid according to claim 2, characterized in that: The pH regulator for adjusting the pH value of the titanium alloy cutting fluid adopts any one of triethanolamine, diethanolamine, diglycolamine and ethanolamine as an organic base.
4. The titanium alloy cutting fluid according to claim 1, characterized in that: The base oil is trimethylolpropane oleate and neopentyl glycol oleate in a mass ratio of 1:0.2-1.
5. The titanium alloy cutting fluid according to claim 1, characterized in that: The nano-lubricating filler is any one of molybdenum disulfide, tungsten disulfide and graphite with a particle size of 20-60nm.
6. The titanium alloy cutting fluid according to claim 1, characterized in that: The nano wetting filler is silicon dioxide with a particle size of 20-60 nm.
7. The titanium alloy cutting fluid according to claim 1, characterized in that: The emulsifier is any one of oleyl alcohol polyoxyethylene ether 1602, oleyl alcohol polyoxyethylene ether 1605, polyethylene glycol 400, and polyethylene glycol 600.
8. A method for preparing a titanium alloy cutting fluid, applicable to the titanium alloy cutting fluid described in any one of claims 1 to 7, characterized in that: The specific steps of the preparation method are: Step 1: pretreatment of fillers, mixing nano-wetting fillers and nano-lubricating fillers into deionized water according to mass fractions, and adding dispersants; Step 2: Ultrasonic stirring treatment, applying ultrasonic power of 200-500W, 500-1000r / min stirring treatment for 30-60min to obtain a dispersion; Step 3: pre-mixing, adding the emulsifier to the dispersion, and simultaneously applying stirring at 200-500 r / min to obtain an emulsifier aqueous solution; Step 4: Add base oil, drop the base oil into the emulsifier aqueous solution at a dropping speed of 1-5 ml / min, and simultaneously apply stirring at 500-800 r / min to form a preliminary emulsion; Step 5: Add additives, add lubricants, corrosion inhibitors, rust inhibitors, defoamers, and fungicides into the preliminary emulsion, stir at 500-800 r / min, and add organic base to adjust the pH to 8-10 to obtain titanium alloy cutting fluid.
9. The method for preparing a titanium alloy cutting fluid according to claim 8, characterized in that: The dispersant is sodium dodecylbenzene sulfonate accounting for 0.5-3% of the total mass of the nano wetting filler and the nano lubricating filler.
10. The method for preparing a titanium alloy cutting fluid according to claim 8, characterized in that: The titanium alloy cutting fluid described in step 5 is homogenized by applying a pressure of 20-50 MPa using a homogenizer and performing the homogenization process 2-5 times.
Citation Information
Patent Citations
Environment-friendly titanium alloy microemulsion cutting liquid
CN102876441B